The analysis of the short and long-term effects of artificial intelligence technology on the cinema film industry - OKUMUŞ, MUHAMMED SAMİ (My University, 2023)
The aim of this study is to show that artificial intelligence technology, which has advanced its development process very rapidly in recent years, has been criticized in the cinema industry for the fact that it reveals the inferences and gains that human beings have achieved in the digital field in a very short time, without the need for labor. In addition to being conceptually discussed, the point that AI technology has reached today and the levels that it is planned to reach or foreseen to achieve in the future will also be discussed methodologically in the scope of this study. This rapid development and transformation is expected to reduce the workforce to minimize costs by eliminating the human factor in many different sectors, on the other hand, it remains unclear whether the original artistic productions and fiction that have emerged so far, especially in the cinema industry, will be transformed into productions that are expected to reach the desired level of success by institutions and platforms on the basis of AI. Within the framework of this study, it is predicted that due to the serious investments made today in AI technology, which will undoubtedly take place in all areas of life in the coming years, it will cause all subjects and values traditionally handled in the social sense, especially in the cinema sector, to change form. Particularly when evaluated on the basis of cinema, it is evaluated that the use of AI in the coming period will lead to job loss of employees serving in many fields in the cinema sector, concern that creative writing will disappear, change in the language and style of cinema, and elements that will drag individuals and institutions into troubled processes in the fields of ethics and copyrights.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC)